2011
DOI: 10.3168/jds.2010-3707
|View full text |Cite
|
Sign up to set email alerts
|

Performance and metabolic profile of dairy cows during a lactational and deliberately induced negative energy balance with subsequent realimentation

Abstract: Homeorhetic and homeostatic controls in dairy cows are essential for adapting to alterations in physiological and environmental conditions. To study the different mechanisms during adaptation processes, effects of a deliberately induced negative energy balance (NEB) by feed restriction near 100 d in milk (DIM) on performance and metabolic measures were compared with lactation energy deficiency after parturition. Fifty multiparous cows were studied in 3 periods (1=early lactation up to 12 wk postpartum; 2=feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

58
260
7
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(329 citation statements)
references
References 27 publications
58
260
7
4
Order By: Relevance
“…The difference between mean BW at calving and nadir BW (−51 kg of weight loss) was expected, due to the typical NEB in early lactation as described by Gross et al (2011), who investigated BW loss and BCS associated with decreased dry matter intake (DMI) leading to mobilization of body reserves. Cumulative yields over the first 100 DIM of multiparous cows were greater (P<0.01) than those of primiparous cows, as it is well established that mature cows produce more milk than first-lactation ones (NRC, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between mean BW at calving and nadir BW (−51 kg of weight loss) was expected, due to the typical NEB in early lactation as described by Gross et al (2011), who investigated BW loss and BCS associated with decreased dry matter intake (DMI) leading to mobilization of body reserves. Cumulative yields over the first 100 DIM of multiparous cows were greater (P<0.01) than those of primiparous cows, as it is well established that mature cows produce more milk than first-lactation ones (NRC, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders of nutritional origin are common in the first months of lactation, because cows are accompanied by a degree of negative energy balance, increasing the rate of mobilization of lipid reserves and increasing concentrations of NEFA and ketone bodies in blood and milk (Gross et al, 2011;Urdl et al, 2015). During periods of herbage shortage and swards with low herbage mass, to control the presentation of nutritional metabolism imbalances and mitigate the effects of an unbalanced diet based on pasture, the use of supplementary food is necessary to ensure a stable supply in quantity and quality of nutrients, in conjunction with proper grazing management (Bjerre-Harpøth et al, 2012;Barrientos et al, 2013;Morales et al, 2014;Ruiz-Albarrán et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In concert with these energy-saving mechanisms, NEFA plasma concentrations are increased indicating that nutrients are provided by lipolysis (Gross et al, 2011;Weber et al, 2013). In addition, a marked elevation (179%) of the growth hormone-releasing and orexigenic peptide hormone ghrelin (Wertz-Lutz et al, 2006;Bradford and Allen, 2008) has been observed in all cows.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, dairy cows experience distinct metabolic stress during periods of high metabolic load and inadequate energy/fuel availability leading to a negative energy balance (NEB), for example, as a result of infectious or metabolic/digestive disorders, during heat stress, and in particular during the transition period around parturition (Gross et al, 2011). Subclinical disorders of the energy metabolism facilitate failure of homeorhetic and homoeostatic adaptations resulting in health problems and reduced performance (Mudron et al, 2005).…”
Section: Introductionmentioning
confidence: 99%